Konkurencyjność wybranych przedsiębiorstw przemysłu mięsnego w opinii konsumentów - Kasprzyk, Aleksander (The Competition of the Chosen Meat Processing Enterprises in the Opinion of Consumers, 2006)
The contemporary market is an assemblage of enterprises which must compete and co-operate one with another on different areas. Marketing orientation is very important. The enterprises investigate growing needs of consumers to satisfy clients' through the offered products and on the other hand to realize their own marks.The instruments of the marketing mix are applied by meat processing enterprises on the market of the south-east region of Poland. The influence of the marketing mix over clients/consumers has a different, but very important effect. These instruments are necessary in building the dominant position of the enterprise on the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 386-392